2012
DOI: 10.1186/bcr3186
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, hormone replacement therapy use and breast cancer risk by age and hormone receptor status: a large prospective cohort study

Abstract: IntroductionAssociations of hormone-receptor positive breast cancer with excess adiposity are reasonably well characterized; however, uncertainty remains regarding the association of body mass index (BMI) with hormone-receptor negative malignancies, and possible interactions by hormone replacement therapy (HRT) use.MethodsWithin the European EPIC cohort, Cox proportional hazards models were used to describe the relationship of BMI, waist and hip circumferences with risk of estrogen-receptor (ER) negative and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
85
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 55 publications
14
85
1
3
Order By: Relevance
“…These findings are consistent with those from two previous large prospective studies which found that the positive association between adiposity and postmenopausal breast cancer risk was more marked in women aged 65 or older6 and in women who had experienced menopause ≥15 years previously 22…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those from two previous large prospective studies which found that the positive association between adiposity and postmenopausal breast cancer risk was more marked in women aged 65 or older6 and in women who had experienced menopause ≥15 years previously 22…”
Section: Discussionsupporting
confidence: 92%
“…Our observed associations with age are in accordance with the findings in the literature for Caucasian women [39]. At a higher age, tumors are more often ER positive [39,40,41,42]. In the study by Parise et al [39], the increase in the percentage of the ER + /PR + /HER2 - subtype with increasing age almost mirrored the increasing proportion of BC cases in white women [39].…”
Section: Discussionsupporting
confidence: 81%
“…Further support of that hypothesis comes from comparing the BMI-breast cancer association among the two major subtypes of breast cancer -those that express estrogen receptors (ER-positive) and those that do not (ER-negative). Excess adiposity has been associated with increased breast cancer risk for ER-positive breast cancers but not for ER-negative breast cancers in most studies, although in a large cohort, the risk for postmenopausal ER-negative breast cancer was also marginally increased by obesity among women who had never used hormone replacement therapy (Ritte et al 2012). Overall, the epidemiologic evidence is compelling that among postmenopausal women, the BMI-breast cancer relationship is driven mostly by the production of endogenous estrogens by aromatase activity in adipose tissues.…”
Section: Breast Cancermentioning
confidence: 99%
“…After menopause, when adipose tissue becomes the primary source of circulating estrogens, the association between excess adiposity and breast cancer risk becomes strongly positive, with progressively increasing risk with increasing BMI (Key et al 2003, Ritte et al 2012. Serum estrogen levels have been shown to be positively associated with breast cancer risk in prospective cohort studies, and postmenopausal hormone replacement therapy increases breast cancer risk, so estrogens and progestins clearly play roles in breast cancer etiology (Key et al 2003, Anderson et al 2004, Endogenous Hormones and Breast Cancer Collaborative Group 2011, Ritte et al 2012.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation